Japanese Foreign Intelligence and Grand Strategy : From the Cold War to the Abe Era - Williams, Brad, 1969- (Book collections on Project MUSE., 2021)
"This book probes the Japanese government's foreign intelligence institutions, practices, and capabilities across the economic, political, and military domains. Brad Williams seeks to explain the relative underdevelopment and distinctiveness of post-1945 Japanese intelligence by exploring the effects of key norms that developed from the experience of World War II and the post-war constitution: bilateralism, developmentalism, technonationalism, and antimilitarism. Japan's role as a key US ally after 1945 is also critical to understanding the functional specialties of Japan's foreign intelligence institutions, particularly in electronic and signals intelligence. Japan's post-1945 national strategy also called for the intelligence community to work hand in hand with Japanese industry to acquire industrial secrets to boost growth and development. Shifts in the international, regional and domestic policy environments in the twenty-first century have contributed to the gradual emergence of a new national security strategy, the Abe Doctrine, which is causing Japan to rethink old norms. As a result, Japan is beginning to rethink the size, shape, and purpose of its intelligence community in light of a rising China. Brad Williams draws upon English- and Japanese-language primary and secondary sources, including declassified files"--